PENERAPAN KONSEP TEORI PERMAINAN (GAME THEORY) DALAM PEMILIHAN STRATEGI KAMPANYE POLITIK (Studi Kasus : Strategi Pemenangan Pemilukada DKI Jakarta Tahun 201 - SAIFUDDIN, AHMAD; TASTRAWATI, NI KETUT TARI; SARI, KARTIKA (E-Jurnal Matematika; Vol 7 No 2 (2018)DO - 10.24843/MTK.2018.v07.i02.p200, 2018)
In Game Theory, generally discusses the zero sum games and non-zero sum games. Both of these studies applied in solving problems predicting the chosen decision based capabilities (pay off). In a case study of the preparation and delivery of the election in Jakarta through the application of the concept of the non-zero sum game obtained by the conclutions that AHY – SM and AB – SU has five same optimum strategies: capture East Jakarta voters, women voters, 20 -29 years old voters, graduated from high school voters, and the Javaness community. While BTP – DSH only different in maximizing strategy of capturing men voters and West Jakarta voters.